A new species of genus Ephemeroporus Frey, 1982 (Cladocera: Anomopoda: Chydoridae) from Peninsular Malaysia - Sinev, Artem Y.; Yusoff, Fatimah M. (Magnolia Press, 2016)
Study of Ephemeroporus Frey, 1982 populations from Peninsular Malaysia revealed a new species. Ephemeroporus malaysiaensis sp. nov. is characterized by the presence of four-five large denticles on anal margin of postabdomen instead of two-three, and five distinctive pigmented spots on each valve. Pigmented spots on the valves were never recorded for any species of family Chydoridae. E. malaysiaensis sp. nov. seems to be another endemic Chydoridae species of South- East Asia. E. malaysiaensis sp. nov. is a rare species, associated with emergent macrophytes in the littoral zone of shallow lake. Most of Ephemeroporus populations from Peninsular Malaysia belong to eurybiotic Paleotropical species Ephemeroporus barroisi (Richard, 1984).